Sunn Hemp—A Promising Cover Crop in Florida - Qingren Wang; Yuncong C. Li; Waldemar Klassen; Edward A. Hanlon (EDIS)
SL-306 (formerly SS-AGR-96), a 4-page illustrated fact sheet by Yuncong Li, Qingren Wang, Waldemar Klassen, Edward A. Hanlon, Jr., describes this green manure crop that has been grown for centuries in Southeast Asia — origin and distribution, description, uses, production and harvest, and seed production. Includes references. Updated with title change by the UF Department of Soil and Water Sciences, September 2015. Minor revision October 2018.